Mouths of rain: An anthology of Black lesbian thought - Jones, Briona Simone (The New Press, 2021)
A groundbreaking collection tracing the history of intellectual thought by Black Lesbian writers, in the tradition of The New Press’s perennial seller Words of Fire “Briona Simone Jones’s anthology Mouths of Rain is an audacious, unapologetic, transgressive collection of Black ‘queer’ writing across genre, time, identity, age, and political leanings. This sister/companion to Words of Fire, published thirty years ago, makes visible—again—our passionate and unwavering commitments to the eradication of all oppressions. It bears witness to the necessity and power of the field of Black Lesbian Studies and is a love offering to us all.” —Beverly Guy-Sheftall, Anna Julia Cooper Professor of Women’s Studies at Spelman College and editor of Words of Fire: An Anthology of African-American Feminist Thought Winner, Publishing Triangle’s Judy Grahn Award for Lesbian Nonfiction Winner, Lambda Literary Award in LGBTQ Anthology African American lesbian writers and theorists have made extraordinary contributions to feminist theory, activism, and writing. Mouths of Rain, the companion anthology to Beverly Guy-Sheftall’s classic Words of Fire, traces the long history of intellectual thought produced by Black Lesbian writers, spanning the nineteenth century through the twenty-first century. Using “Black Lesbian” as a capacious signifier, Mouths of Rain includes writing by Black women who have shared intimate and loving relationships with other women, as well as Black women who see bonding as mutual, Black women who have self-identified as lesbian, Black women who have written about Black Lesbians, and Black women who theorize about and see the word lesbian as a political descriptor that disrupts and critiques capitalism, heterosexism, and heteropatriarchy. Taking its title from a poem by Audre Lorde, Mouths of Rain addresses pervasive issues such as misogynoir and anti-blackness while also attending to love, romance, “coming out,” and the erotic
http://public.eblib.com/choice/PublicFullRecord.aspx?p=6026213
Keywords: anthologie; approches et analyses; hétérosexisme; identités LGBTQIA2+; misogynoir; outils; ouvrages de références; queer; racisme; ressource en ligne; systèmes d'oppressions